PPARβ/δ prevents inflammation and fibrosis during diabetic cardiomyopathy - Adel Rostami; Xavier Palomer; Javier Pizarro-Delgado; Emma Barroso; Brenda Valenzuela-Alcaraz; Fátima Crispi; J. Francisco Nistal; María A. Hurlé; Raquel García; Walter Wahli; Manuel Vázquez-Carrera (Pharmacological Research)
Diabetic cardiomyopathy (DCM) is a specific type of myocardial disease that often develops in patients suffering from diabetes, which has become the foremost cause of death among them. It is an insidious multifactorial disease caused by complex and partially unknown mechanisms that include metabolic dysregulation, local inflammation, fibrosis, and cardiomyocyte apoptosis. Despite its severity and poor prognosis, it often goes undiagnosed, and there are currently no approved specific drugs to prevent or even treat it. Peroxisome proliferator-activated receptor (PPAR)β/δ is a key metabolic regulator that has been proposed as a potential target for DCM due to its pleiotropic anti-inflammatory properties. Diabetes was induced by multiple low-dose streptozotocin (STZ) administration in wild-type and PPARβ/δ knockout male mice treated with the PPARβ/δ agonist GW0742 or vehicle. Human cardiomyocytes (AC16) and mouse atrial myocytes (HL-1) exposed to hyperglycemia and treated with PPARβ/δ agonists were also used. PPARβ/δ deletion in mice negatively impacted cardiac morphology and function, which was accompanied by interstitial fibrosis and structural remodeling of the heart. This phenotype was further exacerbated in knockout diabetic mice. At the molecular level, PPARβ/δ suppression resulted in increased expression of pro-inflammatory and pro-fibrotic markers. Some of these markers were also induced by diabetes in wild-type mice and were exacerbated in diabetic knockout mice. The activity of the transcription factors nuclear factor κB (NF-κB) and activator protein-1 (AP-1) correlated with most of these changes. Remarkably, PPARβ/δ activation partially prevented inflammation and fibrosis in the heart, as well as cardiac atrophy, induced during diabetes in mice, and also in cultured cardiomyocytes exposed to hyperglycemia. Finally, our results suggest that the beneficial effects of PPARβ/δ activation are mediated by the inhibition of mitogen-activated protein kinases (MAPK) activity and subsequent downregulation of the transcriptional activities of NF-κB and AP-1. Overall, the data suggest that PPARβ/δ agonists might be useful in preventing inflammation and fibrosis progression in DCM.